Caracterização espectral como ferramenta no reconhecimento de solo com caráter coeso - Silva, Ana Maria Vieira da (2023)
The spectroscopy technique in order to expose the pedogenetic processes involved in the behavior of soils with a cohesive character has incipient verification. Therefore, the objective of this work was to evaluate the spectral behavior of a soil from a horizon with a cohesive character through the extraction of amorphous material and the application of wetting and drying cycles. To this end, the soil underwent an extraction procedure for amorphous compounds (CE), being compared to the control (SE) by mineralogical characterization (DRX), chemistry (pH, Ca2+, Mg2+, Na+, K+, H+ , Al3+ and C-org), physical (granulometry and sand separation) and spectral in the MIR (FTIR) range. Cylinders of loosened soil were made, housed in steel rings with the same density found in the original soil clods and protected at the base by fabric and elastic, which were subjected to moistening and drying cycles (0, 6 and 12 cycles). After this step, the penetration resistance (RP) of the cylinder and tensile strength (RT) of clods in the upper and lower portions were measured. The following were carried out on the soil of the two plots: granulometric analysis using the micropipette method and spectral measurement in the Vis-NIR-SWIR range. The material after extraction showed an increase in pH, H+, Al3+(due to the acidic power of the oxalate extractant and successive extraction with KCl-1) and Mg2+ (due to the probable destruction of other minerals, indicating a deficiency in the specificity of the extractor). The particle size was significantly affected in CE, mainly due to the agglomeration and hardening of the material during oven drying after extraction, which resulted in an increase in reflectance due to the lower expression of the spectral characteristics of the clay fraction. On average, the lower portion, the 12 cycles and the SE material were the sources of variation that presented the highest RP values. While for RT the highest average values were observed in the CE material and in the lower portion of the cylinders for the 0 and 6 cycle treatments. For the 12 cycle treatment, RT was higher in the CE material, but did not vary between cylinder plots. The difference in reflectance between the two materials reduced as the wetting and drying cycles went by and the spectral features were very similar between the two materials in both spectral bands, differing in a few bands such as 2050 nm in wavelength (VisNirSwir) and in the range of 2000 to 1250 cm-1 in wavenumber (Mir).